Step * 2 1 of Lemma rprod-rminus


1. : ℤ
2. : ℤ
3. {n..m 1-} ⟶ ℝ
4. n ≤ m
5. : ℤ
6. ¬d < n
7. 0 < d
8. (n d) ≤ m
9. rprod(n;(n d) 1;k.-(x[k])) (r(-1)^d rprod(n;(n d) 1;k.x[k]))
10. : ℝ
11. rprod(n;(n d) 1;k.x[k]) v ∈ ℝ
12. v1 : ℝ
13. x[n d] v1 ∈ ℝ
⊢ ((r(-1)^d v) -(v1)) (r(-1)^d v1)
BY
((RWO  "rnexp-add<THENA Auto) THEN RWO  "rnexp1" THEN Auto) }


Latex:


Latex:

1.  n  :  \mBbbZ{}
2.  m  :  \mBbbZ{}
3.  x  :  \{n..m  +  1\msupminus{}\}  {}\mrightarrow{}  \mBbbR{}
4.  n  \mleq{}  m
5.  d  :  \mBbbZ{}
6.  \mneg{}n  +  d  <  n
7.  0  <  d
8.  (n  +  d)  \mleq{}  m
9.  rprod(n;(n  +  d)  -  1;k.-(x[k]))  =  (r(-1)\^{}d  *  rprod(n;(n  +  d)  -  1;k.x[k]))
10.  v  :  \mBbbR{}
11.  rprod(n;(n  +  d)  -  1;k.x[k])  =  v
12.  v1  :  \mBbbR{}
13.  x[n  +  d]  =  v1
\mvdash{}  ((r(-1)\^{}d  *  v)  *  -(v1))  =  (r(-1)\^{}d  +  1  *  v  *  v1)


By


Latex:
((RWO    "rnexp-add<"  0  THENA  Auto)  THEN  RWO    "rnexp1"  0  THEN  Auto)




Home Index